Autobiography of an elderly woman ... - Vorse, Mary Heaton, 1874-1966 (Boston, New York, Houghton Mifflin Company, 1911)
The story of growing old in another age. The time is the early 1910s, the protagonist a grandmother. She complains her children treat her like a child, taking her for walks and car rides to keep her healthy, activities she hates. One can only speculate how grandma would view the modern practice of sending aging relatives to old people's homes.
Shadow of age -- My mother's house -- Conventions of age -- Other people's medicine -- Compensations of age -- Spending of time -- Land of old age -- Grandmothers and grandchildren -- Young people and old -- Unspoken words -- Isolated generation -- Lengthening shadows -- Growing old gracefully.
Mode of access: Internet.
Keywords: Older women -- Fiction; Old age; Fiction